Psychological Well-Being for Women Who Marry Early in Makassar City - Nafiah, Zahrah; Rifani, Rohmah; Hamid, Harlina (Polteknik Ilmu Pemasyarakatan, 2024)
Women who marry early face challenges in their role as wives and maintaining psychological well-being. Adapting to household responsibilities and unstable emotions, along with conflicts, hinder psychological well-being. However, women can achieve psychological well-being with supporting factors. This qualitative study examines the psychological well-being and supporting and inhibiting factors for psychological well-being in women who marry at an early age. This research uses a qualitative method with a case study approach with theory driven data analysis. The research respondents were two 27-year-old women who married at the age of 18. Data collection techniques used interviews and documentation. The results of data analysis show that there are six dimensions of psychological well-being experienced, namely self-acceptance, positive relationships with others, environmental mastery, autonomy, life goals and personal growth. Based on the results of data analysis, there are seven supporting factors for psychological well-being, namely factors of gratitude, optimism, self-control, self-evaluation, life satisfaction, social and environmental support. The results of data analysis also showed six factors inhibiting psychological well-being, namely emotions, mindset, communication, internal pressure, social pressure, and economy. The findings in this study have implications for raising awareness about the problem of early marriage and its impact on women's psychological well-being.